Software-recorded and self-reported duration of computer use in relation to the onset of severe arm–wrist–hand pain and neck–shoulder pain - IJmker, Stefan (BMJ Group, 2010)
OBJECTIVES: In both science and media, the adverse effects of a long duration of computer use at work on musculoskeletal health have long been debated. Until recently, the duration of computer use was mainly measured by self-reports, and studies using more objective measures, such as software-recorded computer duration, were lacking. The objective of this study was to examine the association between duration of computer use at work, measured with software and self-reports, and the onset of severe arm–wrist–hand and neck–shoulder symptoms. METHODS: A 2-year follow-up study was conducted between 2004 and 2006 among 1951 office workers in The Netherlands. Self-reported computer duration and other risk factors were collected at baseline and at 1-year follow-up. Computer use at work was recorded continuously with computer software for 1009 participants. Outcome questionnaires were obtained at baseline and every 3 months during follow-up. Cases were identified based on the transition within 3 months of no or minor symptoms to severe symptoms. RESULTS: Self-reported duration of computer use was positively associated with the onset of both arm–wrist–hand (RR 1.9, 95% CI 1.1 to 3.1 for more than 4 h/day of total computer use at work) and neck–shoulder symptoms (RR 1.5, 95% CI 1.1 to 2.0 for more than 4 h/day of mouse use at work). The recorded duration of computer use did not show any statistically significant association with the outcomes. CONCLUSIONS: In the present study, no association was found between the software-recorded duration of computer use at work and the onset of severe arm–wrist–hand and neck–shoulder symptoms using an exposure window of 3 months. In contrast, a positive association was found between the self-reported duration of computer use at work and the onset of severe arm–wrist–hand and neck–shoulder symptoms. The different findings for recorded and self-reported computer duration could not be explained satisfactorily.